WHAT’S IN A MESSAGE? ANALYSIS OF ANNUAL GRADUATION MESSAGES IN THE PHILIPPINES - Jeremy Velasquez Basilio Velasquez Basilio; Inero Ancho; Gilbert Santos Arrieta (Universitas Islam Negeri Alauddin Makassar, 2020)
What do annual graduation messages convey? What is the gist of the message? What common themes may be derived from these messages? These inquiries inform this study as annual graduation messages issued by the Department of Education (DepEd) Secretary are analysed. This paper recognizes the impact of each graduation message as it serves as a venue in capturing what DepEd attempts to relay to its stakeholders, particularly student graduates in the context of this paper. This study employs qualitative method using data available online. Graduation messages annually issued by DepEd are posted and accessible through online resources. Graduation messages issued from 2010-2019 are utilized in this study. Careful analysis of data reveals the following clustered themes: quality education as the key to transformation, education at the core of life’s challenges, Filipino learners transforming the future, stakeholders and learners towards a better education, and K-12 curriculum as the vehicle for success. Recognition has been given to stakeholders who play crucial roles in the education system and advocate its success. Also, social, cultural, and curricular aspects have also shaped how each graduation message is crafted and relayed to stakeholders.